Genome assisted molecular typing and pathotyping of rice blast pathogen, Magnaporthe oryzae, reveals a genetically homogenous population with high virulence diversity. Issue 9 (September 2021) - Sheoran, Neelam; Ganesan, Prakash; Mughal, Najeeb M; Yadav, Inderjit Singh; Kumar, Aundy
Abstract: Genome sequence-driven molecular typing tools have the potential to uncover the population biology and genetic diversity of rapidly evolving plant pathogens like Magnaporthe oryzae . Here, we report a new molecular typing technique -a digitally portable tool for population genetic analysis of M. oryzae to decipher the genetic diversity. Our genotyping tool exploiting allelic variations in housekeeping and virulence genes coupled with pathotyping revealed a prevalence of genetically homogenous populations within a single-field and plant niches such as leaf and panicle. The M. oryzae inciting leaf-blast and panicle-blast were confirmed to be genetically identical with no or minor nucleotide polymorphism in 17 genomic loci analyzed. Genetic loci such as Mlc1, Mpg1, Mps1, Slp1, Cal, Ef-Tu, Pfk, and Pgk were highly polymorphic as indicated by the haplotype-diversity, the number of polymorphic sites, and the number of mutations. The genetically homogenous single field population showed high virulence variability or diversity on monogenic rice differentials. The study indicated that the genetic similarity displayed by the isolates collected from a particular geographical location had no consequence on their virulence pattern on rice differentials carrying single/multiple resistance genes. The data on virulence diversity showed by the identical Sequence Types (STs) is indicative of no congruence between polymorphic virulence genes-based pathotyping and conserved housekeeping genes-based genotyping. Graphical abstract: Image 1 Highlights: MLST tool is described for population genetic analysis of Magnaporthe oryzae. Loci Mlc1, Mpg1, Mps1, Slp1, Cal, Ef-Tu, Pfk, and Pgk were polymorphic in M. oryzae. Genetically convergent M. oryzae population displayed virulence diversity on rice. Leaf and Neck/Panicle blast inciting M. oryzae were genetically indistinguishable. Neck/Panicle blast inciting M. oryzae isolates showed high virulence diversity on rice.